Karibú (San José, Costa Rica : INDICA, 1983)
Contenido: El heladero / Mercy Cóndor (2 min., 59 sec.) -- No te detengas/Miguel Amadeo (2 min., 55 sec.)
Contenido: Felicumbe / D. R. A.-- Venancio/ Robert Becker (4 min., 53 sec.)
Keywords: GRABACIONES SONORAS; MÚSICA BAILABLE